The changes of β-glucan content during beer production with unmalted pseudocereals - Bogdan, Paulina (Lodz University of Technology Press, 2015)
Unmalted cereals or pseudocereals, including amaranth and quinoa can partially replace malt in beer production. Cereals, such as barley as well as malted grains are rich in β-glucan. During brewing it comes to wort and then is detected in the final product. The β-glucan is known to cause problems during wort and beer filtration, as it increases viscosity. Moreover, high molecular β-glucan may generate turbidity in the final product [1]. On the other hand, it can be advantageous from the nutritional point of view [2]. Substitution of malt with unmalted cereals or pseudocereals may even increase β-glucan content in wort and then in beer. It is connected with: (1) lower amount of malt being used and consequently lower β-glucanase activity, synthesized in grains during malting, (2) higher amount of high molecular polysaccharides coming from grains, which weren’t modified during malting [3]. The purpose of this study was to investigate the changes in β-glucan content during wort and beer production when 10 or 30 % malt was replaced with unmalted quinoa or amaranth.